Eliza: Lessons from Interactive Novels about Publishing in the Era of AI. - Kourkoulou, Dora (Information, Medium & Society: Journal of Publishing Studies, 2023)
This article explores the impact of generative AI and interactive fiction on digital publishing, with a focus on the dialogical and narrative complexities these technologies introduce. Using the interactive novel/game Eliza as a case study, the research explores the illusions of changing definitions of authorship, storytelling, and knowledge production in the context of AI-driven content creation and publishing. The study begins by tracing the historical developments in digital publishing where AI is contributing. It examines how these advancements challenge conventional notions of dialogue and authorship, emphasizing the tendency of AI to promote agreement and flow over conflict and critical engagement. The conceptual framework is dedicated to the role of interactive fiction in redefining narrative dynamics through dialogical elements within digital publishing. The paper analyzes Eliza as a critical example of how interactive games can offer insights into the evolving nature of knowledge production and the dialectical relationships in digital narratives. The game's design and narrative structure, which emphasize player choice and engagement, are explored as reflections of the broader shifts in the publishing industry and making of technology. The article also discusses the methodological considerations for studying narrative frictions in digital games and their implications for publishing studies and understanding technological shifts. It argues that exploring the tensions they reflect is crucial for comprehending how AI and interactive media shape storytelling and content creation. In conclusion, the study posits that AI technologies and interactive fiction are continuing the emphasis on communicative dialogue and synthesis, necessitating a more nuanced understanding of the dialogic and narrative complexities they introduce. It calls for a critical engagement with these technologies to ensure diversity and inclusivity in the future of publishing.